Increased abundance of Sutterella spp. and Ruminococcus torques in feces of children with autism spectrum disorder - Wang, L.; Christophersen, Claus; Sorich, M.J.; Gerber, J.P.; Angley, M.T.; Conlon, M.A. (BMC, 2013)
Background: A recent report indicated that numbers of Sutterella spp. are elevated in gastrointestinal biopsies taken from children with autism spectrum disorder (ASD). We have recently reported changes in the numbers of some bacteria within the stool of ASD children, and now examine whether numbers of Sutterella spp. and some other mucosa-associated bacteria linked with gastrointestinal disease (Ruminococcus gnavus and Ruminococcus torques) are also altered in the stool of these children. Findings. We show that numbers of Sutterella spp. are elevated in feces of ASD children relative to controls, and that numbers of R. torques are higher in the children with ASD with a reported functional gastrointestinal disorder than those without such a disorder. Conclusions: We show further evidence of changes in the gut microbiota of children with ASD and confirm that the abundance of Sutterella spp. is altered in stool. © 2013 Wang et al.; licensee Bio Med Central Ltd.